Reprogramming tumor-associated macrophages with lipid nanosystems reduces PDAC tumor burden and liver metastasis - Palencia Campos, Adrián (2024)
Background: Pancreatic ductal adenocarcinoma (PDAC) requires innovative therapeutic strategies to counteract its progression and metastatic potential. Since the majority of patients are diagnosed with advanced metastatic disease, treatment strategies targeting not only the primary tumor but also metastatic lesions are needed. Tumor-Associated Macrophages (TAMs) have emerged as central players, significantly influencing PDAC progression and metastasis. Our objective was to validate an innovative therapeutic strategy involving the reprogramming of TAMs using lipid nanosystems to prevent the formation of a pro-metastatic microenvironment in the liver.Results: In vitro results demonstrate that M2-polarized macrophages lose their M2-phenotype following treatment with lipid nanoemulsions composed of vitamin E and sphingomyelin (VitE:SM), transitioning to an M0/M1 state. Specifically, VitE:SM nanoemulsion treatment decreased the expression of macrophage M2 markers such as Arg1 and Egr2, while M1 markers such as Cd86, Il-1b and Il-12b increased. Additionally, the TGF-βR1 inhibitor Galunisertib (LY2157299) was loaded into VitE:SM nanoemulsions and delivered to C57BL/6 mice orthotopically injected with KPC PDAC tumor cells. Treated mice showed diminished primary tumor growth and reduced TAM infiltration in the liver. Moreover, we observed a decrease in liver metastasis with the nanoemulsion treatment in an intrasplenic model of PDAC liver metastasis. Finally, we validated the translatability of our VitE:SM nanosystem therapy in a human cell-based 3D co-culture model in vivo, underscoring the pivotal role of macrophages in the nanosystem´s therapeutic effect in the context of human PDAC metastasis.Conclusions: The demonstrated effectiveness and safety of our nanosystem therapy highlights a promising therapeutic approach for PDAC, showcasing its potential in reprogramming TAMs and mitigating the occurrence of liver metastasis.